A New Drug Delivery System Based on Tauroursodeoxycholic Acid and PEDOT1. Issue 9 (15th January 2019) - Carli, Stefano; Fioravanti, Giulia; Armirotti, Andrea; Ciarpella, Francesca; Prato, Mirko; Ottonello, Giuliana; Salerno, Marco; Scarpellini, Alice; Perrone, Daniela; Marchesi, Elena; Ricci, Davide; Fadiga, Luciano
Abstract: Localized drug delivery represents one of the most challenging uses of systems based on conductive polymer films. Typically, anionic drugs are incorporated within conductive polymers through electrostatic interaction with the positively charged polymer. Following this approach, the synthetic glucocorticoid dexamethasone phosphate is often delivered from neural probes to reduce the inflammation of the surrounding tissue. In light of the recent literature on the neuroprotective and anti‐inflammatory properties of tauroursodeoxycholic acid (TUDCA), for the first time, this natural bile acid was incorporated within poly(3, 4‐ethylenedioxythiophene) (PEDOT). The new material, PEDOT—TUDCA, efficiently promoted an electrochemically controlled delivery of the drug, while preserving optimal electrochemical properties. Moreover, the low cytotoxicity observed with viability assays, makes PEDOT–TUDCA a good candidate for prolonging the time span of chronic neural recording brain implants. Abstract : From bears to brain : The Food and Drug Administration approved hydrophilic bile acid tauroursodeoxycholic acid (TUDCA) was successfully incorporated in electrodeposited PEDOT films. This study was aimed at the realization of a new PEDOT–TUDCA composite material that may result a potential substitute of the synthetic glucocorticoids for localized drug delivery system in neuroscience applications.